2013
DOI: 10.1002/ana.23956
|View full text |Cite
|
Sign up to set email alerts
|

Amylin deposition in the brain: A second amyloid in Alzheimer disease?

Abstract: Objectives Hyperamylinemia, a common pancreatic disorder in obese and insulin resistant patients, is known to cause amylin oligmerization and cytotoxicity in pancreatic islets leading to β-cell mass depletion and development of type-2 diabetes. Recent data revealed that hyperamylinemia also affects the vascular system, heart and kidneys. We, therefore, hypothesized that oligomerized amylin might accumulate in cerebrovascular system and brain parenchyma of diabetic patients. Methods Amylin accumulation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
407
4
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 293 publications
(455 citation statements)
references
References 43 publications
19
407
4
7
Order By: Relevance
“…Finally, our findings provide a simple justification for why T2D is a risk factor for PD (as IAPP amyloid seeds, present in T2D, trigger aS amyloid formation), whereas patients with PD are not prone to getting T2D (aS amyloid seeds, present in PD, inhibit IAPP amyloid formation) (36,37). Because aS and IAPP may come in contact with each other both in pancreatic β-cells (33) and in various brain cells (48)(49)(50), and amyloidogenic assemblies may spread from cell to cell (51), in vivo studies are desired to reveal the biological consequences of the cross-reactivity detected here.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, our findings provide a simple justification for why T2D is a risk factor for PD (as IAPP amyloid seeds, present in T2D, trigger aS amyloid formation), whereas patients with PD are not prone to getting T2D (aS amyloid seeds, present in PD, inhibit IAPP amyloid formation) (36,37). Because aS and IAPP may come in contact with each other both in pancreatic β-cells (33) and in various brain cells (48)(49)(50), and amyloidogenic assemblies may spread from cell to cell (51), in vivo studies are desired to reveal the biological consequences of the cross-reactivity detected here.…”
Section: Discussionmentioning
confidence: 82%
“…Despite these facts, putative cross-talk between aS and processed and/or unprocessed IAPP has not been addressed previously. The importance of possible cross-reactivity between these proteins is also underscored by recent reports demonstrating that IAPP is present in brain cells and may form amyloidogenic deposits there, although the IAPP peptide appeared to be synthesized elsewhere (41,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…IAPP deposition has been reported in the gray matter of the temporal lobe in the brains of T2D patients (Jackson et al 2013). IAPP deposits were also found in both blood vessels and perivascular spaces, suggesting an influx from peripheral circulation (Jackson et al 2013). …”
Section: Cross-seeding Between Iapp and Other Protein Aggregates And mentioning
confidence: 99%
“…Although the amount of IAPP injected in this study is substantially higher than the physiological level of IAPP found in the blood, these results strongly suggest that blood can be an effective route for spreading of IAPP aggregates from islet to islet. Furthermore, IAPP deposits positively stained with Congo red were found in blood vessels of the brain from individuals affected by T2D, suggesting that IAPP aggregates might be present in the circulation (Jackson et al 2013). It is generally believed that islets are highly innervated by parasympathetic, sympathetic, and sensory projections (Ahren 2000).…”
Section: Spreading Of Protein Aggregates Within Affected Tissue and Imentioning
confidence: 99%
See 1 more Smart Citation